2019
DOI: 10.3390/cancers11070948
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-CoA Desaturase 1 as a Therapeutic Target for the Treatment of Cancer

Abstract: A distinctive feature of cancer cells of various origins involves alterations of the composition of lipids, with significant enrichment in monounsaturated fatty acids. These molecules, in addition to being structural components of newly formed cell membranes of intensely proliferating cancer cells, support tumorigenic signaling. An increase in the expression of stearoyl-CoA desaturase 1 (SCD1), the enzyme that converts saturated fatty acids to ∆9-monounsaturated fatty acids, has been observed in a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
149
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(163 citation statements)
references
References 184 publications
5
149
1
Order By: Relevance
“…SCD1 is located in the ER of cells in many tissues (lung, pancreas, skeletal muscle, brain, adipose tissue) while SCD5 is only located in brain and pancreas [14][15][16]. Although a compensatory effect was observed in some breast cancer models, SCD5 [8] is not able to restore the effects of SCD1 deficiency [17]. Recently, it has been described that SCD5 is also expressed in the fetal brain of dogs, bovines, and birds [18].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
See 3 more Smart Citations
“…SCD1 is located in the ER of cells in many tissues (lung, pancreas, skeletal muscle, brain, adipose tissue) while SCD5 is only located in brain and pancreas [14][15][16]. Although a compensatory effect was observed in some breast cancer models, SCD5 [8] is not able to restore the effects of SCD1 deficiency [17]. Recently, it has been described that SCD5 is also expressed in the fetal brain of dogs, bovines, and birds [18].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
“…SCD1 overexpression is mediated by LXRs, peroxisome proliferator-activated receptors (PPARs), sterol regulatory element-binding proteins (SREBPs), CCAAT/enhancer-binding proteins (C/EBP)α, etc. [8,23,24]. Curiously, C/EBP also downregulates SCD1 expression in liver and udder during E. coli mastitis and is associated with a SREBP-1 downregulated expression [25].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
See 2 more Smart Citations
“…Affymetrix arrays, qRT-PCR and immunohistochemistry revealed that neonatal hyperoxia inhibited genes needed for de novo fatty acid synthesis in the atrial but not ventricular cardiomyocytes of mice exposed to neonatal hyperoxia. These included Fasn and Scd1, which are elevated in highly proliferative tumors, increase proliferation when overexpressed and required for the proliferation of non-cardiac cells (43)(44)(45)(46)(47)(48)(49). We thus explored whether the persistent repression of Fasn and Scd1 expression is responsible for the reduced proliferation of left atrial cardiomyocytes in mice exposed to neonatal hyperoxia.…”
Section: Discussionmentioning
confidence: 99%